How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen